2011
DOI: 10.1029/2011jd015883
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval of two-layer cloud properties from multispectral observations using optimal estimation

Abstract: [1] A method to derive two-layer cloud properties from concurrent visible, near-infrared, and infrared observations is described. It is a modification of a single-layer scheme and is applied to Spinning Enhanced Visible Infrared Imager (SEVIRI) observations and validated against coincident A-Train data, principally to evaluate the accuracy and characterize cloud top pressure (CTP) estimates. CTP values obtained from the single-layer scheme applied to multilayer clouds are significant overestimates of the upper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
75
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 19 publications
2
75
0
1
Order By: Relevance
“…Davis et al (2009) also showed that the presence of ice clouds can significantly bias the retrievals of liquid cloud properties in the MODIS algorithm (collection 5) (King et al, 1998). Watts et al (2011) confirmed that the simultaneous retrieval of liquid cloud properties can improve retrievals of ice-cloud properties significantly. More recently, a study by Sourdeval et al (2013) also demonstrated that the quality of retrievals of cirrus microphysical and optical properties can be strongly impacted by under-constrained properties of underlying liquid water clouds.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…Davis et al (2009) also showed that the presence of ice clouds can significantly bias the retrievals of liquid cloud properties in the MODIS algorithm (collection 5) (King et al, 1998). Watts et al (2011) confirmed that the simultaneous retrieval of liquid cloud properties can improve retrievals of ice-cloud properties significantly. More recently, a study by Sourdeval et al (2013) also demonstrated that the quality of retrievals of cirrus microphysical and optical properties can be strongly impacted by under-constrained properties of underlying liquid water clouds.…”
Section: Introductionsupporting
confidence: 63%
“…The emergence of such possibilities of synergism was a notable factor in the resurgence of algorithms based on variational methods, such as optimal estimation (e.g. Watts et al, 1998Watts et al, , 2011Hogan, 2008, 2010;Austin et al, 2009;Deng et al, 2010). Such methods indeed prove to be particularly efficient for dealing with large quantities of measurements, in order to retrieve different kinds of cloud parameters.…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of such methods to simultaneously retrieve ice and liquid water cloud properties is still quite rare. It has nevertheless been shown that such algorithms do not only provide a much more complete and coherent description of the atmosphere, but can also improve retrievals of cirrus properties through optimal constraints on properties of liquid water clouds that may lie underneath [6]. This paper presents an algorithm developed to simultaneously retrieve properties of one ice cloud and two liquid water cloud layers.…”
Section: Introductionmentioning
confidence: 99%
“…Many groups are now using optimal estimation techniques to estimate cloud properties (e.g. Heidinger et al, 2010;Watts et al, 1998); however the capability of optimal estimation to include a priori information is not always utilised due to a lack of collocated information of sufficient accuracy and independence. Heidinger et al (2010) have used climatological data as a priori information with mixed results, OCA (optimal cloud analysis) and ORAC use European Centre for Medium-range Weather Forecasting (ECMWF) ERA Interim reanalysis sea surface temperature data as a priori to the surface temperature state vector.…”
Section: Introductionmentioning
confidence: 99%
“…The ORAC (Optimal Retrieval of Aerosol and Cloud) algorithm (Poulsen et al, 2012;Watts et al, 1998) employs the optimal estimation approach (Rogers, 2000) based on radiometric retrieval principles and has been extensively applied to the Along Track Scanning Radiometer Instruments (ATSR), specifically ATSR-2 (1995, Mutlow et al, 1999 and the Advanced-ATSR (2002, LlewellynJones et al, 2001. The radiometric configuration of ATSR-2 and AATSR comprises seven channels at 0.…”
Section: Introductionmentioning
confidence: 99%